"PEDAGOGIC AND DIDACTIC POSSIBILITIES OF USING MINIATURE WORKS IN HISTORICAL LESSONS" - Amirkulovich, Khaydarov Sulaymon (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the didactic possibilities of increasing the effectiveness of History Education by using historical and visual arts in secondary education schools.One of the important tasks is to use the fine arts in modern methods of teaching historical science. It will improve the practical knowledge and skills, effectively organize students' independent work, increase their interest in history, and modernize the lesson process. Therefore, the development of scientific, pedagogical, methodological foundations and conditions for use of historical works of fine art is a topical issue today.The article aims to develop pedagogical requirements for the use of historical art works in the lessons of history, creating a didactic system to enhance the historical memory of schoolchildren through the use of miniatures with a true depiction of historical chronicles, enhancing the effectiveness of historical education through documentary evidence.The article provides the necessary conclusions as to justification of the relevance of the topic raised and the extent of its work.The topic raised in this article is not only educational but also educational. For example, the practice of using miniature artworks in History classes shows that enhancing students' historical knowledge and skills for self-image can also produce positive results in instilling in students a sense of national pride and patriotism.